2022
DOI: 10.1021/acsaelm.2c00766
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap, Mobility, Dielectric Constant, and Baliga’s Figure of Merit of 4H-SiC, GaN, and β-Ga2O3 from 300 to 620 K

Abstract: Bandgap, mobility, and dielectric constant are important parameters to measure the properties of an opto-electric semiconductor material. Here, this work evaluates the temperature dependence of these basic parameters of the third-generation wide-bandgap semiconductors including 4H-SiC, GaN, and β-Ga 2 O 3 , based on which Baliga's figure of merit (BFOM = ε r × μ × E g 3) is obtained correspondingly. Experimental results indicate that as temperature increases, compared with that of 4H-SiC and GaN, the bandgap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The bandgap, dielectric constant, and carrier mobility have a significant role in Baliga's figure of merit (B FOM ), which represents a very important parameter in determining the properties of (UWBG) semiconductors in optoelectronic and power electronics applications. 20 Therefore, the enhancement of these parameters, i.e., bandgap and dielectric constant of UWBG ZGO, is very important for the evaluation/improvement of the performance of power semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…The bandgap, dielectric constant, and carrier mobility have a significant role in Baliga's figure of merit (B FOM ), which represents a very important parameter in determining the properties of (UWBG) semiconductors in optoelectronic and power electronics applications. 20 Therefore, the enhancement of these parameters, i.e., bandgap and dielectric constant of UWBG ZGO, is very important for the evaluation/improvement of the performance of power semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…Wide-bandgap elemental semiconductor diamond (Eg = 5.5 eV) and compound semiconductors, β-Ga 2 O 3 (Eg = 4.9 eV), GaN (Eg = 3.4 eV), and ZnO (Eg = 3.35 eV), combine visible light transparency and high carrier mobility as well as high-temperature operational stability and a strong power-handling capability, and are usually applied in ultraviolet (UV) photodetectors, high-power electron devices, and transparent electronics [1][2][3][4]. The wurtzite structure Mg x Zn 1−x O (x ≤ 0.25) is a wide-bandgap ternary oxide semiconductor system with unique characteristics, such as intrinsic blindness to the visible light and radiation toughness, as well as low-temperature synthesis and wet-etch availability [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the BFOMs of a-Ga 2 O 3 is 1.64 times higher than that of b-Ga 2 O 3 , indicating superior performance of a-Ga 2 O 3 and demonstrating its potential for use in nextgeneration power electronics. [9][10][11] The devices and the processing of b-Ga 2 O 3 have been extensively studied; however, few studies have been thus far reported on the devices and processing of a-Ga 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%